DIGITAL CULTURE MATURITY ASSESSMENT CASE STUDY AT DANONE AQUA (The Indonesian Journal of Business Administration, 2021)
Founded in 1973, AQUA Group is the pioneer of Bottled Drinking Water (AMDK) in Indonesia, which then established a strategic partnership with Danone in 1998. Danone Aqua has been implementing the digital transformation about 8 years. Initially the priorities were to improve the efficiency of many internal processes and ways of working, and the motivations behind this initial transformation were principally for the benefit of its business operation, rather than the customers’ experience (although benefits can be mutual). Currently their digital transformation already covered in many aspects of business.In this study, the author tried to assess the digital culture maturity of Danone Aqua as initial picture of their digital transformation that have been implemented since 8 years ago, to identify the strengths as well as weaknesses of digital transformation elements, to identify the gaps and key areas focus improvement. The study using digital culture model from Daniel Rowles. Quantitative survey conducted to determine the digital culture maturity, it involved 107 managerial level staff. Qualitative survey conducted to confirm the quantitative result, it involved key stakeholder of digital transformation.Base on quantitative and qualitative study, the author able to conclude that the digital transformation at Danone Aqua particularly Operation division has been implemented in proper level. It shown by good level of digital culture maturity at 79% and it has level four – process measured and controlled.Keywords: Digital transformation, Digital culture model, Digital skill, System - Technology.